Spray deposition on onion crops and soil according to spray nozzle and working pressure - Amler, Dionatan Alan; Amler , Fabrício Flávio; Silva , Jamille Santos da; Guerra, Naiara; Oliveira Neto, Antonio Mendes de (Revista de Ciências Agroveterinárias, 2021)
Pesticide application has been researched and improved over the years, yet there is still a lack of research related to the application technology on onion crops. This work aimed to evaluate the interaction of different spray nozzles and working pressures on the spray deposition on onion plants and the soil. The experiment consisted of sixteen treatments and five replicates, carried out in a 4 x 4 factorial scheme, combining four spray nozzles (MF 110 015, AD 110 015, TT 110 015, and ADIA 110 02) and four working pressures (207 kPa, 276 kPa, 345 kPa, and 414 kPa). The assay was carried out in a greenhouse with onions plants transplanted in pots with a volume of 8 dm-3 with soil. Fully developed onion plants with five to six leaves and soil-conditioned Petri dishes were the biological targets for assessing the spray deposition on the plants and the soil. Bright blue coloring was used as a tracer and, after the application, it was recovered with distilled water and quantified using a spectrophotometer to determine the deposition. Spray deposition on the onion plants was affected only by the spray nozzle factor, while deposition on the soil was influenced by the spray nozzle model, working pressure, and the interaction between them. We concluded that the impact (TT 110 015) and air induction (ADIA 110 02) nozzles were the models that presented the highest spray deposition on the onion plants and the soil. The working pressure did not influence the spray deposition on the onion plants. The increase in working pressure raised the spray deposition on the soil for the flat fan (MF 110 015), pre-orifice (AD 110 015), and air induction (ADIA 110 02) nozzles but did not affect the deposition with the impact nozzle (TT 110 015).